Accounting based measurements with regards to investors' reactions to M&A : an empirical study to establish profile of target firms. - Chan, Priscilla Jia Hui. (2008)
This paper explores the relationship between positive market reactions and M&As events with accounting-based measurements. Financial ratios obtained based on motivations for M&A are used to establish the profile of a target firm.